PENGARUH MODEL PROBLEM-BASED LEARNING BERBASIS CONTROVERSIAL ISSUES PADA PEMBELAJARAN IPA TERHADAP KETERAMPILAN ARGUMENTASI ILMIAH SISWA SMP - Supeno Supeno; Miftahul Hasanah; Ulin Nuha (FKIP e-PROCEEDING, 2022)
Scientific argumentation is one of the skills students really need in this century. Learning science by involving argumentation skills will provide opportunities for students to build knowledge and understanding with all the right information, link between stigmas, and improve thinking skills. The reality in the field is that students still have difficulty in developing their argumentation skills. In an effort to improve scientific argumentation skills, several learning innovations are needed that can go hand in hand with indicators of scientific argumentation skills in building students' familiarity with these skills. Therefore, this study aims to determine the effect of using the controversial issues-based Problem-Based Learning model on students' scientific argumentation skills. The sample used in this study was 64 class VII students of SMP N 7 Jember with a quasi-experimental research design in which the control class and the experimental class were randomly selected. Students' argumentation skills were measured using a post-test after several science learning meetings were held by applying the problem-based learning model accompanied by controversial issues in the experimental class. The results showed that there were differences in scientific argumentation skills in the experimental class using PBL learning based on controversial issues. Evidenced by the significant influence of controversial issues-based PBL on students' scientific argumentation skills based on accumulated data on the average mean value in the experimental group (79.94) and in the control class (62.82), data on improving scientific argumentation skills is strengthened by the value of the independent t-test. In the t-test sig.(2-tailed) is at 0.000 where <0.05 this indicates that there is a difference between the control class and the experimental class.